TEACHING WRITING STRATEGIES USED BY ENGLISH TEACHERS AT MAN 2 KAMPAR - Syafira Dwi Asmita; Ridwan; Alwen Bentri; Fetri Yeni J. (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The objective of this research is to find out the strategies that teacher used in teaching writing at MAN 2 Kampar and its implementation. The method of this research was qualitative research. The subject of this research was English teacher in MAN 2 Kampar. Interview was used as its research instrument. The result of the research found that the teacher implemented chart strategy in teaching writing. Through the implementation of the strategy, the teacher is able to know how far the students could understand the material that the teacher has given and able to do the assignment as well.